DEVELOPMENT OF METHODOLOGICAL PREPARATION OF FUTURE PRIMARY TEACHERS FOR INTEGRATIVE TEACHING USING MODERN PEDAGOGICAL TECHNOLOGIES - Jurayeva, Nargiza (E-Library Karshi SU, 2025)
This article discusses the problems of the modern education system, the potential of teaching staff, the social significance of the development of methodological training of future primary school teachers for integrative education, as well as the use of modern pedagogical technologies in improving their methodological preparation for integrative education. information has been analyzed.